Graded Channel MOSFET simulation with S-Pisces 2B - Siswono, Hartono (Makara Journal of Technology, 2004)
Graded Channel MOSFET simulation with S-Pisces 2B. Graded-Channel Metal-Oxide-Semiconductor Field-effect- Transistor or GCMOSFET is being discussed in this paper. GCMOSFET technology has been developed to meet the growing demand for low power and high performance application. In this paper, it will be shown that, compared to ungraded MOSFET, the GCMOSFET device offers the advantage of significantly higher drive current. The higher drive current is achieved because the effecctive channel length of GCMOSFET is shorter than the ungraded MOSFET’s. From the simulation result with S-PISCES 2B and MATLAB, it can been shown that the ID from GCMOSFET is higher than the ID from ungraded MOSFET. As an example, with VG = 4 V and VD = 4 V, ID from MOSFET is equal with 9.78 e-06 A and ID from GCMOSFET is equal with 16.56 e-06 A. Beside that, as an example, to get ID = 1.13 e-05 A with MOSFET will need VG = 4 V and VD = 4.7 V, and with GCMOSFET VG = 4 V and VD = 1.2 V will be needed. This result has shown that GCMOSFET needs lower supply voltage than the ungraded MOSFET which means that GCMOSFET needs lower power consumption than ungraded MOSFET. From the simulation results, it can be proved that GCMOSFETwith shorter LGC (graded channel region length) will give larger ID than ID from GCMOSFET with longer LGC. As we can see that for VGS = 4 V and VDS = 2 V, GCMOSFET with LGC = 4 μm will give ID = 16,56E-06 A, GCMOSFET with LGC = 3,5 μm will give ID = 17,51E-06 A, and GCMOSFET with LGC = 3 μm will give ID = 18,49E-06